Mobilitätsverhalten von Menschen mit Migrationshintergrund in Deutschland. Annäherungen an eine unbekannte Größe am Beispiel von Offenbach am Main. - Welsch, Janina (My University, 2019)
In der Arbeit wird die Frage gestellt, ob sich Menschen mit Migrationshintergrund unter den hiesigen Rahmenbedingungen in ihren Mobilitätsvoraussetzungen und in ihrem alltäglichen Mobilitätsverhalten von den Menschen ohne Migrationshintergrund unterscheiden. Darüber hinaus ist die Identifikation wichtiger Einflussfaktoren zur Erklärung des Verhaltens von besonderem Interesse. Grundlage ist eine - teilweise explorativ angelegte - empirische Studie zum Mobilitätsverhalten von Menschen mit und ohne Migrationshintergrund in Offenbach am Main, die 2010 im Rahmen eines Forschungsprojekts am Institut für Landes- und Stadtentwicklungsforschung (ILS) durchgeführt wurde. Die Ergebnisse zeigen sowohl Gemeinsamkeiten als auch Unterschiede zwischen den Gruppen. Diese betreffen soziodemografische und -ökonomische Faktoren, mobilitätsbezogene Voraussetzungen wie Führerscheinbesitz oder Verkehrsmittelverfügbarkeit, Fragen zur Mobilitätskultur im Elternhaus, aber vor allem die alltägliche Nutzung verschiedener Verkehrsmittel. Die Ergebnisse werden in Artikelform kumulativ präsentiert und nach einer thematischen Einführung eingeordnet und im Zusammenhang diskutiert.

The current and the predicted demographic change in Germany can be described by a trend towards ageing but also towards an internationalisation and diversification of society. The proportion of people with a non-German origin has been rising for years. In the population statistics those persons are categorised as having an immigration background, according to their own and their parent´s nationality. In the German mobility and transport sciences there is only very scarce and fragmented knowledge about this population group. Little is known about the existence of preconditions for the use of different transport means such as driver´s license ownership or the ability to ride a bicycle. Also, little is known about the availability of different transport means or about everyday travel behaviour. This gap is particularly striking in comparison with the USA. Here, transport, education and health sciences increasingly study the travel behaviour of immigrants. The aim of this thesis is to reduce this knowledge gap for Germany. One of the main questions is, whether people with an immigration background differ from people without an immigration background in their mobility options and in their everyday travel behaviour. In addition, the identification of important influencing factors for the explanation of behaviour is of particular interest. The base of this thesis is an empirical study on the travel behaviour of people with and without an immigration background in Offenbach am Main. It was conducted in 2010 as part of a research project at the ILS - Institute for Regional and Urban Development Research (ILS - Institut für Landes- und Stadtentwicklungsforschung gGmbH). The results show both similarities and differences between the groups. Differences relate to sociodemographic and socio-economic factors, to mobility-related preconditions such as driver´s licence ownership or availability of transport means, to the family´s mobility culture, but above all to the everyday use of different transport means. In the cumulative thesis the results are presented in article form. The framing text introduces the topic, links it to existing literature, gives details on the empirical study and discusses the findings in context.
Travel behaviour of people with an immigration background in Germany - approaching the unknown by the example of Offenbach am Main.
Keywords: Individualverkehr; Mobilität; Mobilitätsverhalten; Verkehrsverhalten; Alltag; Verkehrsmittelwahl; ÖPNV; Personenkraftwagen; Fahrradverkehr; Migrant; Sozialisation; Empirische Untersuchung; Fallstudie; Exploration; Verkehrsangebot; Wohnstandort; Bevölkerungsstruktur; Bevölkerungsstatistik; Migrationshintergrund